Effect of fermentation conditions on the chemical composition, peptides, texture and volatile compounds of Turkish bag sausage (Torba sucuk) - Tekin, Ali; Kanmaz, Hilal; Kaya, Büşra; Sulejmani, Erhan; Hayaloğlu, Ali Adnan (Elsevier Ltd, 2025)
The aim of the study is to characterize the effects of curing conditions on the chemical composition, peptides, texture and volatile components of Arapgir bagged sausage (torba sucuk). For this purpose, two batches of dry fermented sausages (sucuk), R (room or natural, at 25 °C, 28 % relative humidity) and C (controlled cabin condition, 15 °C, 42 %), were analyzed over the storage days (0, 3, 7 and 14 days after fermentation). The highest acidity or lowest pH was found in R sucuk during fermentation (P<0.05). DPPH antioxidant activity was significantly higher in the C sucuks than R sucuks at the days 3 and 14 of fermentation (P<0.05). The RP-HPLC peptides were at higher extent in the C sucuk than in the R sucuk. A total of 55 volatiles were characterized and the total content of volatile substances after 14 days of fermentation was higher in the C sucuk than in the R sucuk. The fermentation method under controlled cabin condition (C) resulted in firmer, less brittle and stiffer sucuks than the natural production method (R). The results show that the use of the C method in the production of torba sucuk improves the volatile profile, texture and bioactivity of the sucuk samples. © 2024
Keywords: Controlled cabin; Fermentation conditions; Proteolysis; Textural properties; Torba sucuk; Volatiles